KNOWLEDGE OF PREGNANT WOMEN ABOUT THE DANGERS OF HYPERTENSION IN THE WORK AREA PUSKESMAS TANJUNGBATU, KUNDUR DISTRICT - Nurul Widiati; Arum Dwi Anjani (Universitas Batam, 2020)
Background : Hypertension is one of the biggest health problems in Indonesia, this is evidenced by the frequency with which it is found in primary health services in Indonesia with a fairly high prevalence of 25.8%. Based on the results of measurement of blood pressure, the prevalence in people over 18 years of age was 31.7% in 2007 and according to provinces in Indonesia, the highest was South Kalimantan with 39.6% and the lowest was West Papua with 20.1%. In 2013, hypertension decreased by 5.9% from 31.7% to 25.8%, this decline could occur due to several factors such as different measurement tools, people who are starting to become aware of the importance of health and people who are starting to understand about the danger of hypertension. The 5 provinces with the highest prevalence of hypertension in absolute numbers / people according to the 2013 Riskesdas, namely Bangka Belitung province with 30.9%, South Kalimantan 30.8%, East Kalimantan 29.6%, West Java 29.4% and Gorontalo with 29.4. % (Ministry of Health, Republic of Indonesia, 2014). The purpose of this study was to determine the knowledge of pregnant women about the dangers of hypertension in the working area of the Tanjungbatu Public Health Center, Kundur District. Method :This study used a descriptive research design. The research site will be conducted at the Tanjungbatu Kundur Community Health Center, Karimun Regency, Riau Islands. The population in this study were all pregnant women in the Tanjungbatu Public Health Center, totaling 160 people. Result : It can be seen that there is an average score on the knowledge of pregnant women about the dangers of hypertension, namely 1.1613 with 20 questions and 62 respondents conclusion : an average score on the knowledge of pregnant women about the dangers of hypertension, namely 1.1613 with 20 questions and 62 respondents.